PENGARUH PENDAPATAN, PENDIDIKAN, DAN JUMLAH TANGGUNGAN KELUARGA TERHADAP POLA KONSUMSI RUMAH TANGGA NELAYAN DI DESA BATU BELUBANG KABUPATEN BANGKA TENGAH - Ratih Agustinningrum, Nesa Pebriani, Sheilla, Pathul Kirom (Universitas Teuku Umar, 2024)
This research was conducted with the aim of finding out the influence of Income, Education and Number of Family Dependents on the Consumption Patterns of Fisherman Households in Batu Be Lubang Village, Central Bangka Regency. The data used is primary data sourced from questionnaires distributed to 76 respondents. Then the data was analyzed using the multiple linear regression equation, Classic Assumption Test, t test, F test, and regression coefficient (R2). The research results obtained show that the income variable has a positive and significant effect on the household consumption variable, the education variable shows a negative relationship and a significant effect that is not too big on the consumption variable, while the variable number of family dependents shows a positive relationship but does not have a significant effect that is not too big on the consumption variable. household consumption. Then, based on the results of the t test and F test, it was found that income, education and number of family dependents had a significant effect on household consumption in Batu Bejiwa village, Central Bangka Regency. The coefficient of determination test result (R2) is 43.38%, which means that income, education and number of family dependents have an influence of 43.38% on fishermen's household consumption and the remaining 56.62% is influenced by other variables.